Taxation of Annual Income as a Commitment Device - Thomas Gaube (Verein für Socialpolitik, 2010)
I study a two-period model of nonlinear, information constrained income taxation. It is shown that time-consistent taxation of annual income welfare-dominates time-consistent taxation of lifetime income if preferences are such that stationary allocations are efficient. If uncertainty is taken into account and if state-contingent fiscal policy is not feasible, time-consistent taxation of annual income can also welfare-dominate taxation of lifetime income under commitment. These findings may help in explaining why governments usually tax annual rather than lifetime earnings.
Keywords: H21; H24; H31; 330; nonlinear income taxation; tax base; time-consistency; commitment